BREATH HOLDING TIME AND OXYGEN SATURATION IN COVID AFFECTED NURSING STUDENTS-A COMPARATIVE STUDY - KOMMAREDDY, SRAVANI; KIRANMAYI, PENTAKOTA; RAGAM, RAVISUNDER; BABU K, RAMESH (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The present study is based on a novel approach of validated breath-holding technique and efficiency of SpO2 in the adverse COVID-19 outcomes and comparison with normal subjects. Methods: It is a prospective observational study conducted in residential/private nursing colleges, St. Luke’s School and College of Nursing and Smt. Vijaya Luke’s College of Nursing, Visakhapatnam during the period July 2021. Fifty-three student nurses affected with mild COVID-19, 35 student nurses affected with moderate COVID-19, aged 18–23 years were enrolled after taking thorough history about COVID-19 that is after 2 months of complete recovery. They were classified based on the symptom history in which the subjects without symptoms or mild symptoms were taken as mildly affected, whereas subjects with severe symptoms with mild fluctuations in SpO2 who didn’t require hospitalization were classified as moderately affected. The study included 109 normal control cases who are never affected with COVID-19 viral infection. In all the subjects, the oxygen saturation was measured using pulse oxymeter and their Breath holding times were also measured using standard protocols. Results: The mean value of BHT was significantly reduced from normal 16.7339±3.4 to 12.8571±5.1 (p<0.05) in moderate cases. When oxygen saturation levels were compared before and after the breath holding in normal, mild and moderate cases the results were significant. However, when the oxygen saturation levels were compared between normal and mild COVID-19 cases the values were insignificant (p=0.4) and at the same time when the oxygen saturation levels were compared between normal and moderate COVID-19 cases the values were significant (p=0.0001). Conclusion: According to the findings, breath-holding does not need greater energy expenditure or cardiac output, and it eliminates walking and the related contamination of bystanders as occurring with pulse oximeter. Breath holding time is a determinant of respiratory capacity, when used as parameter helps in assessing the progression of lung injury, it gives an idea about respiratory fitness especially in this COVID era. Breath holding time and fluctuations in SpO2 when used conjointly we can assess degree of lung damage so that further treatment such as the continuity of medication, practicing of breathing exercises with or without medical treatment can be planned. This simple non-invasive tool can be used for the self-assessment of improvement in post-Covid patients. Future validation studies validate this hypothesis, measurement of these basic, innovative surrogates requires minimum inventory (i.e., a means to record oximetry and a timing device) and could feasibly provide a useful way to evaluate risks of future deterioration under under-resourced conditions.